2014
DOI: 10.1017/jfm.2014.80
|View full text |Cite
|
Sign up to set email alerts
|

On the laminar–turbulent transition of the rotating-disk flow: the role of absolute instability

Abstract: This paper describes a detailed experimental study using hot-wire anemometry of the laminar–turbulent transition region of a rotating-disk boundary-layer flow without any imposed excitation of the boundary layer. The measured data are separated into stationary and unsteady disturbance fields in order to elaborate on the roles that the stationary and the travelling modes have in the transition process. We show the onset of nonlinearity consistently at Reynolds numbers, $R$, of $\sim $510, i.e. at the onset of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 32 publications
5
58
3
Order By: Relevance
“…Malik (1986), Lingwood (1995a), Pier (2003), and experimental studies, e.g. Wilkinson & Malik (1985), Lingwood (1996), Othman & Corke (2006), Siddiqui et al (2013), Imayama, Alfredsson & Lingwood (2014a), have focused on various aspects of the instability characteristics and laminar-turbulent transition. There have also been several investigations of the turbulent rotating-disk flow, e.g.…”
Section: Figure 1 (Colour Online)mentioning
confidence: 99%
“…Malik (1986), Lingwood (1995a), Pier (2003), and experimental studies, e.g. Wilkinson & Malik (1985), Lingwood (1996), Othman & Corke (2006), Siddiqui et al (2013), Imayama, Alfredsson & Lingwood (2014a), have focused on various aspects of the instability characteristics and laminar-turbulent transition. There have also been several investigations of the turbulent rotating-disk flow, e.g.…”
Section: Figure 1 (Colour Online)mentioning
confidence: 99%
“…Figure 1 in Imayama, Alfredsson & Lingwood (2014) shows typical examples of laminar velocity profiles from rotating-disk boundary-layer flow. Here, quantities U * , V * , W * , r * , z * , θ and the non-dimensional quantities, U, V, W, R, z are defined as † Email address for correspondence: lingwood@mech.kth.se in Imayama et al (2014), where * denotes a dimensional value. The inflection point of the radial velocity profile makes the flow inviscidly unstable, so-called cross-flow (or Type-I) instability.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of the authors' knowledge no such experiments have yet taken place. Certainly in the Newtonian regime a wealth of literature exists, and this is currently a topic of particular interest, see Imayama et al [22][23][24], for example. Personal communication with these authors has revealed the difficulty of obtaining consistently accurate experimental results; therefore we can only envisage that the introduction of non-Newtonian fluids would serve to significantly complicate any experimental procedure.…”
Section: Discussionmentioning
confidence: 99%